2019
DOI: 10.1038/s41467-019-12099-4
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation but not ALS mutations in FUS rewires motor neuron metabolism

Abstract: Energy metabolism has been repeatedly linked to amyotrophic lateral sclerosis (ALS). Yet, motor neuron (MN) metabolism remains poorly studied and it is unknown if ALS MNs differ metabolically from healthy MNs. To address this question, we first performed a metabolic characterization of induced pluripotent stem cells (iPSCs) versus iPSC-derived MNs and subsequently compared MNs from ALS patients carrying FUS mutations to their CRISPR/Cas9-corrected counterparts. We discovered that human iPSCs undergo a lactate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 69 publications
6
53
0
Order By: Relevance
“…In addition, fibroblasts from sALS patients showed a different response to ageing compared to controls as an increase in uncoupled mitochondrial respiration, but no decrease in glycolysis, no increase in the oxygen consumption rate or in extracellular acidification rate were observed [80]. Finally, we recently showed that ALS-causing mutations in FUS do not affect cellular respiration in human motor neurons [9]. Altogether, these studies illustrate the value of the Seahorse XF analyzer and its ability to obtain reliable information about mitochondrial respiration and extracellular acidification.…”
Section: Extracellular Metabolic Flux Analysismentioning
confidence: 90%
See 4 more Smart Citations
“…In addition, fibroblasts from sALS patients showed a different response to ageing compared to controls as an increase in uncoupled mitochondrial respiration, but no decrease in glycolysis, no increase in the oxygen consumption rate or in extracellular acidification rate were observed [80]. Finally, we recently showed that ALS-causing mutations in FUS do not affect cellular respiration in human motor neurons [9]. Altogether, these studies illustrate the value of the Seahorse XF analyzer and its ability to obtain reliable information about mitochondrial respiration and extracellular acidification.…”
Section: Extracellular Metabolic Flux Analysismentioning
confidence: 90%
“…In our opinion, the latter indicates that mitochondrial dysfunction could represent a general hallmark of ALS rather than being attributed to mutations in SOD1. Yet, we recently showed that mitochondrial dysfunction is absent in FUS-ALS human motor neurons [9]. Thirdly, evidence points to a defective carbohydrate metabolism in ALS.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations